What Is the Relation Between the Corporate Governance and The Shareholders in Germany? – A Brief Literary Overview - Nina K. GOGOLL (Communications of International Proceedings, 2023)
Sustained corporate scandals are not in the interests of the shareholders. Corporate governance structures are supposed to reduce agency problems. The impression arises that the role of the shareholder(s) within corporate governance are too ambitious. Thus, the research question arises, what is the relation between corporate governance and its shareholder(s) in Germany. To find answer, this article follows the methodology of the formal-analytical research strategy with the simple and more or less abstract describing of problem structures (cp. Grochla, 1978, p. 85) by presenting the challenges of corporate governance and its economic scandals in the recent years and analyzes the role of the shareholder(s). This strategy is complemented by the secondary research method. The findings are that corporate governance is still supposed to reduce the agency problems and it requests national-specific setup due to legal reasons, e.g. in Germany. The activist shareholder, derived from the monistic system, is challenged by the dualistic corporate constitution of the German stock corporation with delineation of competencies of the management board, supervisory board and shareholders’ meeting as well as shareholder activism tries to demonstrate impact, form or change management decisions. Furthermore, the pursuit of shareholder value is assumed to be the major driver of shareholder activism, beside the alignment of executive compensation with shareholder interests and an efficient market for corporate control that can be tied up to the shareholders’ interests. Also, working corporate governance can lead to the impacts of achieving and maintaining competitive advantages and long-term growth in corporate value.
Keywords: Corporate Governance; Shareholder; Corporate Value; Reporting